If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 4096 Reorder the terms: 3 + 2x = 4096 Solving 3 + 2x = 4096 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 4096 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 4096 + -3 2x = 4096 + -3 Combine like terms: 4096 + -3 = 4093 2x = 4093 Divide each side by '2'. x = 2046.5 Simplifying x = 2046.5
| 4x-5y-2y+x= | | 7(2x-5)=63 | | 2x-1-y=4 | | 8w-47=5(w-7) | | -4(y-2y)+7=-6(2y-y)+4+9y | | 7(a-6)+14=2(a-4) | | 390=R-.25R | | 2y=c+ay | | 4x-6(4-x)=14 | | 7xwhat=1 | | (x+2)*(x-2)= | | -160=-40x | | (x+2)*(x-2)=x^2 | | r-(-18)=-68 | | 113.68=196-196r | | 2m-13=-8m-20 | | x^2-5.5x+2.5=0 | | 15-(-x)=80 | | 2-5y=0 | | 25-55+(85+65)= | | 5=-1(3-9x) | | 4x-2(6-3x)=8.2 | | 8y-(7y-142)=51 | | -2c(-2c-12)=2c-12 | | -x+3y=-6-x | | -2(5.25+6.2x)=4(-3.1x+2.58) | | -7(-w+3x-5)= | | 3(5q-8)=3q | | m^6+6m^3+24m^2+72m-167=0 | | x^2+(m^3+3)x-6m^2-18m+44=0 | | 21.882+4.9=4.2(1.8n+3.69) | | y(x^2+xy-2y^2)dx+x(3y^2+xy-x^2)dy=0 |